2012
DOI: 10.1371/journal.pone.0048768
|View full text |Cite
|
Sign up to set email alerts
|

An N-Myristoylated Globin with a Redox-Sensing Function That Regulates the Defecation Cycle in Caenorhabditis elegans

Abstract: Globins occur in all kingdoms of life where they fulfill a wide variety of functions. In the past they used to be primarily characterized as oxygen transport/storage proteins, but since the discovery of new members of the globin family like neuroglobin and cytoglobin, more diverse and complex functions have been assigned to this heterogeneous family. Here we propose a function for a membrane-bound globin of C. elegans, GLB-26. This globin was predicted to be myristoylated at its N-terminus, a post-translationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…The remaining SRP genes include a Myb-like/SANT-like transcription factor (Sro94_g048900), a metallopeptidase (Sro489_g153380), a gene encoding a transmembrane protein containing an EF-hand domain (Sro1_g000260) and a globin (Sro2353_g324460) ( Figure 4C). The latter gene is especially interesting as, next to their oxygen binding capabilities, globins are increasingly implicated in redox signaling 65,66 . When exploring ROS signaling related genes, the conventional DE analysis uncovered an NADPH oxidase (NOX, Sro1572_g283390) with a pronounced MT+ specific response to SIP (Figure 3), catalyzing extracellular production of superoxide anions by moving an electron from NADPH through the plasma membrane to molecular oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining SRP genes include a Myb-like/SANT-like transcription factor (Sro94_g048900), a metallopeptidase (Sro489_g153380), a gene encoding a transmembrane protein containing an EF-hand domain (Sro1_g000260) and a globin (Sro2353_g324460) ( Figure 4C). The latter gene is especially interesting as, next to their oxygen binding capabilities, globins are increasingly implicated in redox signaling 65,66 . When exploring ROS signaling related genes, the conventional DE analysis uncovered an NADPH oxidase (NOX, Sro1572_g283390) with a pronounced MT+ specific response to SIP (Figure 3), catalyzing extracellular production of superoxide anions by moving an electron from NADPH through the plasma membrane to molecular oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Although, palmitoylation occurs mainly close to the N-terminus of proteins, it has also been observed in other parts of proteins 87 , 88 . Globin proteins associated with the membrane have been identified in some bacteria 44 - 47 , in the nematode Caenorhabditis elegans 89 , in the shore crab Carcinus maenas 48 , and recently also in vertebrates 49 , 50 . However, there is no evidence that these globins share common ancestry suggesting that membrane-associated globins arouse independently several times in the course of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Besides GLB-12, 2 other globins appear to play a role in redox signaling, namely GLB-6 and GLB-26. 34,35 …”
Section: Globins Can Actively Drive Redox Signalingmentioning
confidence: 99%
“…Previous results of our group indicated that GLB-26 has a role in redox signaling. 34 GLB-26 is exclusively expressed in the stomato-intestinal and anal depressor muscle cell and in the head mesodermal cell, all of which appear to be associated with the regulation of the defecation cycle. We observed that the defecation cycle is normal in a glb-26 knockout strain, but is differentially affected in WT and glb-26 knockout worms when they are exposed to high concentrations of a ROS producing compound.…”
Section: Globins Can Actively Drive Redox Signalingmentioning
confidence: 99%